Return to me ebook The restoration chronicles series, book 1. - Austin, Lynn (The Restoration Chronicles, 2013)
After years in exile, Iddo and his grandson Zechariah follow God's leading home to Jerusalem, where they struggle to rebuild their lives and God's temple.